Modern forest-climatic conditions and forest typological zoning of Kazakhstan - Nazarenko Nazar; Panina Maria; Sherstobitov Yuri (E3S Web of Conferences)
For the Republic of Kazakhstan, forest climatic and forest typological zoning was performed based on current meteorological data of the early 21st century using forest climatic indices of D.V. Vorobyov and D.D. Lavrinenko. The spatial extent of forest typological zones is shown in connection with the influence of the Caspian Sea and mountain systems of Central Asia, as well as a complex forest typological mosaic determined by the contrast of the temperature regime. The existence of some clitopes previously determined by extrapolation is confirmed. The presented scheme of forest clitopes and zoning can be used in planning and organizing forest management, silvicultural and forestry activities.